2016
DOI: 10.1002/jso.24364
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with nipple-sparing mastectomy: A prospective study of patient reported outcomes using the BREAST-Q

Abstract: Background and Objectives The authors sought to study patient-reported outcomes following nipple-sparing mastectomy (NSM). Methods From 2008 to 2011, the BREAST-Q was administered to women undergoing NSM surgery for cancer treatment or risk-reduction prior to surgery and at two years after completion of reconstruction. The change in score over time and the impact of surgical indication, complication occurrence and laterality on scores were analyzed. Results The BREAST-Q was prospectively administered to 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 26 publications
(35 reference statements)
2
48
0
Order By: Relevance
“…Our NSM patients found that they were more likely to feel sexually attractive and fulfilled as compared to those patients undergoing SSM. Previous studies that examined these domains after NSM have found comparable raw BREAST‐Q scores . Raw scores for psychosocial well being ranged from 83.2‐86, satisfaction with breast from 66.2‐73 and sexual well being raw score ranged from 57 to 65.5 .…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Our NSM patients found that they were more likely to feel sexually attractive and fulfilled as compared to those patients undergoing SSM. Previous studies that examined these domains after NSM have found comparable raw BREAST‐Q scores . Raw scores for psychosocial well being ranged from 83.2‐86, satisfaction with breast from 66.2‐73 and sexual well being raw score ranged from 57 to 65.5 .…”
Section: Discussionmentioning
confidence: 87%
“…There are other studies that have examined NSM patients using the BREAST‐Q . While these studies have found similar results for the NSM patients in the patient reported outcomes, there has been variability in the study designs.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations